(untitled) (European Journal of Marketing and Economics, 2019)
There is no sales document as crucial to winning business deals as the business proposal document. We noticed that business proposals try their best to be persuasive, and yet, they do not have the impact they hope to create. In order to understand why we conducted detailed research and found out that customers simply refuse to read some proposals. There are three reasons for this: Logic, Clarity, and Aesthetics. Our research showed that the lack of logic or the presence of logical fallacies account was the reason most often quoted by customers (63% of the times) for not wanting to read the business proposal, followed by clarity, at 29% and aesthetics at 9%. To write this research paper, we’ve focused primarily on understanding logical fallacies, categorizing them and identifying which of them are the most identifiable and which of them are most frequent. We also recommend a systematic way to avoid logical fallacies in proposals.